PENGARUH PELAYANAN PUBLIK TERHADAP KEPUASAN MASYARAKAT: STUDI KASUS IZIN PRODUKSI PANGAN INDUSTRI RUMAH TANGGA DI KANTOR BADAN PENANAMAN MODAL KOTA BATU - Delly Indriani; Sugeng Rusmiwari; Agung Suprojo (Universitas Tribhuwana Tunggadewi, 2018)
Abstrac: Basically, public service is an effort to fulfill public needs, with the main purpose for the satisfaction of society. However, the public services provided by the service providers still do not meet the public satisfaction. This study aimed to determine how big was the influence of public service to the level of satisfaction felt by the community. This research used quantitative descriptive research and the data collection techniques used questionnaires, documentation, observation. The population of this research was the society that became customer of Batu’s Investment Board. The sample in this study amounted to 20 people by using Purposive Sampling. The data quality test consisted of validity and reliability test and using simple regression analysis method. Result of research indicated that service quality 67,25%. Based on the hypothesis test using SPSS 16.0, the value of t arithmetic was 2,674 with significance value 0,015